The importance of socialization is to live Silih Asih, Silih Asah, and Silih Asuh as a Strengthening of Religious Tolerance in The Village of Palalangon - Novianti, Delpi; Sirait, Rajiman Andrianus (Journal of Community Service and Society Empowerment, 2023)
The multicultural diversity of Indonesia is a gift to be preserved in harmony and unity.As societies in the practice of religion want peace, harmony and abundance in the exercise of each other's beliefs without any pressure and intimidation from the surrounding environment. The village of Palalangon, which is in the Ciranjang district, Cianjur district is an area that upholds high values of tolerance. This paradigm is based on the methods of implementation in the service of this society by observation, interview and socialization from house to house conducted to the government (to the people), the figures of the community (ad/sepuh) religious figures, and some communities. Palalangon is a village located in Ciranjang county, Cianjur county is one of the villages in which the majority of Christians live. Palalangon itself entered the territory of Kertajaya or entered in the government of kertajaya. There are at least 15 ethnic groups in the village of Kertajaya.Some of the indicators of success in socialization include the ability to express the attitudes of religious tolerance that should continue in everyday life and the values of Silih Asih, Silih Asah, and Silih Asuh can be noble values for the realization and development of the attitude of religion's tolerance.